Plasticity and habitat choice match colour to function in an ambush bug. (3rd February 2020) - Boyle, Julia; Start, Denon
Abstract: Individuals aim to maximize their fitness by matching their own phenotype to the optimum phenotype in their environment. Individuals can achieve matching through several mechanisms including habitat choice and adaptive plasticity. A key trait of interest to biologists is colour, with background matching reciprocally camouflaging predators and prey. However, the multiple mechanisms matching an individual's colour to their background, and its consequences for function (e.g. species interactions), are rarely explored simultaneously. Here we investigate colour variation in ambush bugs, Phymata americana, that feed on insects visiting white and yellow flowers. We conducted surveys of wild populations to establish phenotype–environment matching and its effects on prey capture, then performed habitat choice and plasticity (colour change) trials to test for the mechanisms underlying putative patterns of habitat matching. Ambush bugs matched their background—yellower ambush bugs were found on yellow flowers and whiter ambush bugs on white flowers, and matching increased prey capture. This pattern was seemingly driven by a combination of plasticity and habitat choice. Our study highlights how organisms can optimize trait values through a combination of plasticity and habitat choice with tangible effects on individual performance. We suggest that multiple mechanisms interactively shape phenotypes, optimizing function and fitness in the wild. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.